PENGEMBANGAN MODEL LITERASI KESEHATAN LINGKUNGAN DALAM MENJAGA EKOSISTEM LAHAN GAMBUT SECARA BERKELANJUTAN - Dessyka Febria (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2018)
This article discusses the development of a model of environmental health literacy to maintain a sustainable ecosystem on peatlands. In maintaining the peatland sustainable ecosystem, an environmental health literacy model is needed so that the community can follow up on the health of the surrounding environment. To make informed decisions, communities must have the ability to obtain, process and understand health and environmental information. The approaches used in environmental health literacy are [1] Basic, and functional literacy with efforts to evaluate environmental health information, [2] communicative interactive and awareness literacy in reducing health and environmental risks and [3] improving quality of life and protecting the environment with provide education so as to change people's behavior. Ultimately, efforts to develop this model of environmental health literacy are intended to prevent the occurrence of peatland ecosystem damage and are able to empower communities through increased understanding of health risks and environmental risks that affect health and the environment.